2012
DOI: 10.4049/jimmunol.1202062
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 Restores Lymphocyte Functions in Septic Patients

Abstract: Septic syndrome is the leading cause of mortality for critically ill patients worldwide. Patients develop lymphocyte dysfunctions associated with increased risk of death and nosocomial infections. In this study, we performed preclinical experiments testing the potential of recombinant human IL-7 (rhIL-7) as a lymphostimulating therapy in sepsis. Circulating IL-7 and soluble IL-7 receptor α-chain (soluble CD127) concentrations were measured in plasma, whereas cellular CD127 expression was evaluated on circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 25 publications
9
134
0
5
Order By: Relevance
“…A lower expression and especially failure of restoration of HLA-DR expression appear indicative of immunoparalysis, as it is related to the susceptibility to opportunistic infections and outcome in sepsis patients [15]. Several promising immuno-adjuvant agents are slated for testing in the near future, including GM-CSF (ClinicalTrials.gov identifier: NCT02361528), IL-7, anti-PD-L1 (ClinicalTrials.gov identifier: NCT02576457), and thymosin-alpha-1 [2,8,12,13,16,17]. Given the remarkable success of immunotherapy in cancer and the similarities in the immune defects in cancer and sepsis patients [18], it appears plausible that immunotherapy may represent a major advance in the treatment of this highly lethal disease.…”
Section: How Should Development Of Immunosuppression Impact Clinical mentioning
confidence: 99%
“…A lower expression and especially failure of restoration of HLA-DR expression appear indicative of immunoparalysis, as it is related to the susceptibility to opportunistic infections and outcome in sepsis patients [15]. Several promising immuno-adjuvant agents are slated for testing in the near future, including GM-CSF (ClinicalTrials.gov identifier: NCT02361528), IL-7, anti-PD-L1 (ClinicalTrials.gov identifier: NCT02576457), and thymosin-alpha-1 [2,8,12,13,16,17]. Given the remarkable success of immunotherapy in cancer and the similarities in the immune defects in cancer and sepsis patients [18], it appears plausible that immunotherapy may represent a major advance in the treatment of this highly lethal disease.…”
Section: How Should Development Of Immunosuppression Impact Clinical mentioning
confidence: 99%
“…IL‐7 is a multifunctional cytokine of the immune system that affects both T cells and B cells and induces the proliferation of naïve and memory T cells 44. Venet et al45 showed that IL‐7 treatment of isolated lymphocytes from septic patients restored T‐cell proliferation and IFN‐γ secretion.…”
Section: Immunological Modification Therapiesmentioning
confidence: 99%
“…[65][66][67][68][69][70] Ex vivo treatment of lymphocytes from patients with sepsis with IL-7 signifi cantly improved T-cell proliferation, up-regulation of anti-apoptotic proteins, and IFN-γ production capacity. 63 Whereas rhIL-7 is currently being evaluated in patients with chronic viral infection and cancer, to date it remains unstudied in vivo in the setting of critical illness.…”
Section: Adaptive Immune Stimulating Agentsmentioning
confidence: 99%